A Profile of the University for the Next Millenium - Infante, Vidal Sunción (Education Policy Analysis Archives, 1999)
In this article, I analyze the role of the university in meeting the demands for new knowledge (scientific, artistic and technological) presented by an era of globalization of knowledge that is destroying old paradigms and creating new models of management and behavior. These demands include the need to train new professionals, who are highly skilled both in knowing "how to produce" as well as "why to produce." My recent research indicates that the university is not embarked on the path that leads to training professionals who know "how to produce." Nevertheless, I believe that it is possible to restructure the university to meet these goals. Activities and strategies are being devised to increase the university's ability to generate the basic knowledge that will increase the employability of the new professional with a university diploma.